2006
DOI: 10.1038/sj.bjc.6603435
|View full text |Cite
|
Sign up to set email alerts
|

NFV, an HIV-1 protease inhibitor, induces growth arrest, reduced Akt signalling, apoptosis and docetaxel sensitisation in NSCLC cell lines

Abstract: HIV-1 protease inhibitor (PI), nelfinavir (NFV) induced growth arrest and apoptosis of NCI-H460 and -H520, A549, EBC-1 and ABC-1 non-small-cell lung cancer (NSCLC) cells in association with upregulation of p21 waf1 , p27kip1 and p53, and downregulation of Bcl-2 and matrix metalloproteinase (MMP)-2 proteins. We found that NFV blocked Akt signalling in these cells as measured by Akt kinase assay with glycogen synthase kinase-3a/b (GSK-3a/b) as a substrate. To explore the role of Akt signalling in NFV-mediated gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 40 publications
1
63
0
Order By: Relevance
“…The HPI doses required in vitro to block PDGF-induced Akt phosphorylation and PA-SMC proliferation were also similar to those of the specific PI3K inhibitor LY294002 and to those of the HPIs shown in previous studies to inhibit tumor cell growth and to block Akt signaling. [12][13][14] Thus, our finding that the HPIs inhibited Akt suggests mediation of HPI effects by inhibition of GSK3 phosphorylation, ie, GSK3 activation. Accordingly, cell treatment with a GSK3 inhibitor completely abolished the growthinhibiting effects of amprenavir, nelfinavir, and LY294002 and markedly decreased the inhibitory effect of ritonavir.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…The HPI doses required in vitro to block PDGF-induced Akt phosphorylation and PA-SMC proliferation were also similar to those of the specific PI3K inhibitor LY294002 and to those of the HPIs shown in previous studies to inhibit tumor cell growth and to block Akt signaling. [12][13][14] Thus, our finding that the HPIs inhibited Akt suggests mediation of HPI effects by inhibition of GSK3 phosphorylation, ie, GSK3 activation. Accordingly, cell treatment with a GSK3 inhibitor completely abolished the growthinhibiting effects of amprenavir, nelfinavir, and LY294002 and markedly decreased the inhibitory effect of ritonavir.…”
Section: Discussionmentioning
confidence: 85%
“…[12][13][14] The PI3K-Akt axis is a major pathway for cell proliferation and cancer. This pathway is often activated in tumor cells but not in normal host cells and may therefore hold considerable promise as a target for future treatments against cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such concentrations correspond to the C max (w7-9 mmol/l) for NFV in HIV patients. Experiments with animal models of human cancers have demonstrated that at clinically achievable concentrations, NFV inhibited tumor growth (Pore et al 2006, Yang et al 2006, Gills et al 2007, Shim et al 2012. NFV contains a unique cis-decahydroisoquinoline-2-carboxamide moiety, which may provide the structural basis for its increased efficacy against cancer compared with other HIV protease inhibitors.…”
Section: Medications For the Treatment Of Infectious Diseasesmentioning
confidence: 99%